Clinicopathologic features and risk factors for hepatocellular carcinoma: Results from a single center in southern Turkey - Birol ÖZER; Ender SERİN and Uğur YILMAZ and Yüksel GÜMÜRDÜLÜ and Özlem SAYGILI and Fazilet KAYASELÇUK and Sedat BOYACIOĞLU (Turkish Journal of Gastroenterology, 2019)
-